Genome-Wide Characterization of miRNAs Involved in Gene-Mediated Immunity in Response to Tobacco Mosaic Virus in - Kangquan Yin; Yang Tang; Jinping Zhao (Evolutionary Bioinformatics, 2015)
microRNAs (miRNAs) are a class of endogenous small RNAs (sRNAs) that play pivotal roles in plant development, abiotic stress response, and pathogen response. miRNAs have been extensively studied in plants, but rarely in Nicotiana benthamiana , despite its wide use in plant virology studies, particularly for studying N protein-tobacco mosaic virus (TMV) interactions. We report an efficient method using high-throughput sequencing and bioinformatics to identify genome-wide miRNAs in N. benthamiana. A total of 30 conserved miRNA families and 113 novel miRNAs belonging to 93 families were identified. Some miRNAs were clustered on chromosomes, and some were embedded in host gene introns. The predicted miRNA targets were involved in diverse biological processes, such as metabolism, signaling, and responses to stimuli. miRNA expression profiling revealed that most of them were differentially expressed during N-mediated immunity to TMV. This study provides a framework for further analysis of miRNA functions in plant immunity.